Pembelajaran Sejarah Asia Timur dengan Metode Inkuiri pada Program Studi Pendidikan Sejarah STKIP Sinar Pancasila - Augusta De Jesus Magalhaes; Simon Ukasa Manek (Pusat Riset dan Inovasi Nasional, 2026)
This research is one of the efforts of history educators to improve the quality of learning of East Asian History courses in the History Education Study Program of STKIP Sinar Pancasila which takes place in semester 3, through the use of inquiry methods in classroom learning activities, it is hoped that it can create a meaningful history learning atmosphere. The application of this learning model can foster enthusiasm and a sense of curiosity to learn in students so that students are trained to find out, discover, and solve problems they face during the learning process through the use of inquiry methods. In this study, the method used is qualitative research with the study strategy being classroom action. Using strategies because many opinions have emerged that the quality of learning will be conducive if implemented by teachers by paying attention to every activity that has been carried out during the learning process such as determining learning objectives, compiling materials to be taught, searching for and collecting sources used as references in the preparation, learning strategies to be used, time allocation and evaluation activities. The inquiry approach implemented begins with an expository approach, where the lecturer plays a major role in the learning activities, particularly in terms of coaching, providing direction, guiding students, providing action, and leading to evaluation and reflection activities. It ends with an inquiry approach where students are required to be more independent during the process of searching, discovering, and solving problems related to the issues posed by the lecturer.